Analysis Of Unemployment, Inflation Rate, And Investment On The Number Of Poor Populations In North Sumatra Province, 1991 – 2020 - PUTRY SIAGIAN (Outline Journal of Economic Studies, 2024)
Poor people are residents who have an average monthly per capita expenditure below the poverty line. The problem of poverty is a complex and multidimensional problem covering various aspects in the clinic of human life, including the local government in North Sumatra. This study aims to analyze most of the effects of unemployment, inflation, and investment on the poor in North Sumatra in the 1991-2020 period, both simultaneously and partially. The data used by the equipment were obtained from the official website of the Central Statistics Agency (BPS) of North Sumatra. The results of this study are a) unemployment has a positive and significant effect on poverty in North Sumatra Province, b) inflation has a positive and significant effect on poverty in North Sumatra Province, c) Investment has a negative and significant effect on poverty in North Sumatra Province, and d) simultaneously unemployment, investment and inflation have a significant effect on poverty in North Sumatra Province. The R-Squared value of 0.763154 means that as much as 76.31 percent of the variable contribution to the number of poor people can be explained through stimulus, inflation and investment variables. While the remaining 23.69% is influenced by variables not examined. Keywords: Unemployment, Inflation Rate, Investment, Poor Populations